Variabilidade espacial do solo em um gramado de futebol - Amaral, Andervan (2014)
Are incipient the studies on fields sports using tools to precision agriculture (PA). The aim of this study was to evaluate the spatial variability of soil properties in a pitch football, using PA techniques, in order to provide enhancements to the lawn. The study was conducted on a pitch football with dimensions of 100m x 70m belonging to Itapagé Esporte Clube in the city of Frederico Westphalen (RS). The area was divided into a sampling grid of 10 x 7m, totaling 100 sampling points, where samplings were carried out in depth from 0.00 to 0.10 m. The attributes analyzed were : clay content, phosphorus ( P ), potassium ( K ), pH in water and organic matter (OM ). The attributes were analyzed using descriptive statistics, obtaining the position measurements (minimum, average and maximum) of dispersion (standard deviation, coefficient of variation, coefficient of skewness and kurtosis coefficient) and checking the existence of central tendency data (normality). The values of coefficient of variation (CV) were classified as low (CV < 15 %), medium (15 < CV < 35 %) and high (CV > 35 %) variability. To spatial characterization of the soil properties (clay, phosphorus, potassium, pH and organic matter in water) were generated thematic maps and maps correction for P and K. The models have been structured using kriging interpolation method by means of Surfer 11® software. The use of PA tools was useful for characterization of soil properties on the lawn of previously established football. Clay contents ranged between 36 and 61 %. P and K showed high and medium spatial variability respectively, requiring correction variable rate whereas soil pH and organic matter showed low and medium spatial variability, respectively. The actions resulting from this research can contribute to the management of pitch football in Brazil.